Antimicrobial activities and phytochemical profile of the leaf extracts of Barringtonia racemosa L. (Putat) against selected pathogens: An ethnomedicinal plant species - Jeffry M Saro; Jacob E Josue; Noel P Sastrillas; Almay Rose Joy C Gundaya; Mary Grace A Valencia; Rommel R Rimando; John Mark C Sarongon; Leila A Allado-Ombat (Open Journal of Plant Science - Peertechz Publications, 2022)
Barringtonia racemosa L. (Putat) was mostly utilized as a treatment for wound infections and other types of skin diseases locally. The leaves of B. racemosa are traditionally used to treat high blood pressure and as a depurative. This study aimed to assess the antimicrobial activities and phytochemical profile of the leaf extracts of Barringtonia racemosa L. (Putat) against selected pathogens. The ethanolic extracts of the leaves were explicitly prepared and applied to two Gram-positive bacteria (Staphylococcus aureus and Bacillus cereus), whereas the Gram-negative bacteria (Escherichia coli) used the disc diffusion method based on the standard procedure. Moreover, among the test microorganisms, only the Gram-positive bacteria were sensitive to the ethanolic extracts of Barringtonia racemosa L. with the diameter of zone of inhibition ranging from 13.81±0.96 mm to 14.85±0.57 mm. The findings of this study suggested that the tribes could explicitly continue utilizing this ethnomedicinal plant as a source of treatment. Thus, the ethanol extracts of the leaves of B. racemosa were found to be effective against several pathogens used in this study, which certainly highlights the potential extremity of herbal drugs and their possible use as local medicine. Hence, there has been a continuing search for new and more potent antibiotics.